FEEDING IS A MAJOR COMPONENT OF LIVESTOCK PRODUCTION TECHNOLOGY - Tsvigun , А. Т.; Іоnov , І. А; Tsvigun, О.А (Podilian Bulletin: Agriculture, Engineering, Economics, 2022)
The main principles of scientific and methodological approaches to the normalization of animal feeding are studied in 15 monographs, reference books and manuals, 39 recommendations and 19 patents and copyright certificates. World and domestic approaches to the normalized feeding of farm animals have been studied. Strategic directions of normalized animal feeding have been developed, which include organizational, methodological and practical measures. The creation of a unified scientific and methodological center for animal nutrition and a network of analytical laboratories is substantiated. For the development of normalized animal feeding, it is proposed to develop and implement a modern methodology for animal nutrition rationing based on NRC principles and approaches, to develop and implement technologies for the management of the feeding and development of high-performance animals, with further justification of detailed animal feeding standards